ANALISIS PUTUSAN BEBAS DALAM KASUS KEBAKARAN HUTAN OLEH PT KUMAI SENTOSA (STUDI KASUS PUTUSAN NOMOR 233/PID.B/LH/2020/PN.PBU) - Reyhan Raesandi; Mella Ismelina Farma Rahayu (Fakultas Hukum Universitas Tarumanagara, 2022)
The State has obligation to maintain and utilize natural resources wisely and responsibly, besides, The State is also responsible for guaranteeing the right to a prosperous life born and inner, to reside, and to obtain a good and healthy living environment for its people, as stated in the 1945 Constitution of the Republic of Indonesia. Today, we still encounter environmental conditions that continue to experience destruction in almost all regions in Indonesia. Ministry of Environment and Forestry says, forest and land fires are still the biggest problem in environmental problems. However, one of the courts in Indonesia with Decision Number 233/Pid.B/LH/2020/Pn.Pbu has decided to acquit PT Kumai Sentosa for allegedly burning forest and land in Central Kalimantan. What was the judge’s reasoning on the case? Is the judge's decision in the case appropriate for the fulfillment of environmental protection efforts? The author examines the problem by using normative legal research methods. The research show that there’s an injustice in the decision, especially in the context of environmental protection efforts because the judge tends to be biased in deciding this case, as can be seen from the existence of several things that are ignored for consideration by the Panel of Judges. It is better if the court, which has an important role in fulfilling the environment, must be more careful in deciding cases related to the environment, because in this case the acquittal of PT Kumai Sentosa could set a bad precedent for environmental protection efforts in Indonesia’s future.